FOSS4G 2018 Conference Highlights. Issue 2 (2nd September 2018) - Quill, Theresa; Djenno, Mireille
Abstract : The Free and Open Source Software for Geospatial (FOSS4G) conference took place in Dar es Salaam, Tanzania in August 2018. The theme of "Leave No One Behind" centered the conference on issues of diversity and inclusion, and included a wide range of presentations. This article presents a review of FOSS4G2018 from the perspectives of a GIS Librarian and an African Studies Librarian.